Acmonidesite, a new ammonium sulfate chloride from La Fossa crater, Vulcano, Aeolian Islands, Italy. (29th May 2018) - Demartin, Francesco; Castellano, Carlo; Campostrini, Italo
Abstract: The new mineral acmonidesite, (NH4, K, Pb 2+, Na)9 Fe4 2+ (SO4 )5 Cl8, was found in an active fumarole (fumarole FA, temperature 250°C) at La Fossa crater, Vulcano, Aeolian Islands, Sicily, Italy. It occurs on a pyroclastic breccia as brown prismatic crystals up to 0.10 mm long, in association with salammoniac, alunite and adranosite. The mineral is orthorhombic, space group C 2221 (no. 20) with a = 9.841(1), b = 19.448(3) c = 17.847(3) Å, V = 3415.7(9) Å 3 and Z = 4. The six strongest reflections in the powder X-ray diffraction pattern are: [ d obs in Å( I )( hkl) ] 8.766(100)(110), 1.805(88)(390), 5.178(45)(131), 4.250(42)(221), 2.926(42)(330) and 2.684(32)(261). The empirical formula (based on 28 anions per formula unit [pfu]) is (NH4 )5.77 K1.42 Pb0.62 Na1.24 Fe3.96 Mn0.08 S5.04 O20.16 Cl7.97 Br0.08 . The idealised formula is (NH4, K, Pb 2+, Na)9 Fe4 2+ (SO4 )5 Cl8 . The calculated density is 2.551 g cm –3 . Using single-crystal diffraction data, the structure was refined to a final R ( F ) = 0.0363 for 4614 independent observed reflections [ I > 2σ( I) ]. The structure contains two independent, distorted octahedral iron sites, Fe1 and Fe2, with the iron atoms in the 2+ oxidation state, as confirmed by the interatomic distances and bond-valence calculations (2.06 and 1.94 vu, respectively). Fe1 is surrounded by two chlorine atoms and four oxygens of the sulfate ions, with the following average distances (Å): Fe1–O 2.125 and Fe1–Cl 2.472; and Fe2 is surrounded by three chlorine atoms and three oxygens of the sulfate ions, with the following average distances (Å): Fe2–O 2.110 and Fe2–Cl 2.531. Three independent sulfate anions are also present and are connected with the iron polyhedra to form a three-dimensional structure containing voids occupied by four independent ammonium ions (two of them partially replaced by K + ), one Na + /Pb 2+ site and one Cl – ion.